Respuesta :
f(x)=x²+2x-1 and g(x)=2x-4 2f(x)-3g(x)=?
2f(x)=2*(x²+2x-1)=2x²+4x-2
3g(x)=3(2x-4)=6x-12
2f(x)-3g(x)=(2x²+4x-2) - (6x-12)= 2x²+4x-2 - 6x+12 =2x²-2x +10
2f(x)-3g(x) = 2x²-2x +10
2f(x)=2*(x²+2x-1)=2x²+4x-2
3g(x)=3(2x-4)=6x-12
2f(x)-3g(x)=(2x²+4x-2) - (6x-12)= 2x²+4x-2 - 6x+12 =2x²-2x +10
2f(x)-3g(x) = 2x²-2x +10
Composite functions involve combining more than one functions
The value of 2f(x) - 3g(x) is [tex]2x^2 -2x-+ 10[/tex]
We have:
[tex]f(x) = x^2 + 2x - 1[/tex]
[tex]g(x) =2x - 4[/tex]
The value of 2f(x) - 3g(x) is calculated as follows:
[tex]2f(x) - 3g(x) = 2 \times f(x) -3 \times g(x)[/tex]
Substitute the values of f(x) and g(x)
[tex]2f(x) - 3g(x) = 2 \times (x^2 + 2x -1) -3 \times (2x - 4)[/tex]
Open brackets
[tex]2f(x) - 3g(x) = 2x^2 + 4x -2 -6x + 12[/tex]
Collect like terms
[tex]2f(x) - 3g(x) = 2x^2 + 4x -6x-2 + 12[/tex]
[tex]2f(x) - 3g(x) = 2x^2 -2x-+ 10[/tex]
Hence, the value of 2f(x) - 3g(x) is [tex]2x^2 -2x-+ 10[/tex]
Read more about composite functions at:
https://brainly.com/question/19695569